The Effect of Empowering Leadership and Leader-Member Exchange on Employee Performance - Wan Medi; Adi Rahmat; Helwen Heri (SAINS ORGANISASI, 2023)
BPJS Ketenagakerjaan nationally has experienced an increase in quantity, such as an increase in the number of employees, prospective employees, the number of participants, payment of claims, and even in terms of the number of work accidents and deaths of participants has also increased. In terms of quality, such as the satisfaction of BPJS Ketenagakerjaan participants based on the survey, it has also increased. This means that every year there are improvements in the service and management performance of BPJS Ketenagakerjaan. However, in addition to improving operational performance both qualitatively and quantitatively, there were also internal problems, especially from the leadership aspect. The subjects of this study were employees working at the BPJS Ketenagakerjaan in the West Sumatra Regional Office. The population in this study were all employees at the BPJS Ketenagakerjaan Regional Office of West Sumatra, totaling 154 people. The number of samples in this study was 61 respondents and the sample was taken by random sampling method, namely taking random samples which were considered to represent all employees. Based on the results of the analysis, several conclusions can be drawn: 1) Empowering leadership influences the performance of BPJS Ketenagakerjaan employees at the West Sumatra Regional Office. 2) Empowering leadership influences the leader-member exchange (LMX) of BPJS Ketenagakerjaan employees at the West Sumatra Regional Office. 3) Leader-member exchange (LMX) influences the performance of BPJS Ketenagakerjaan employees at the West Sumatra Regional Office. 4) Empowering leadership and leader-member exchange (LMX) jointly influence the performance of BPJS Ketenagakerjaan employees at the West Sumatra Regional Office.